Dual-Wavelength Light Emission from CdSe/ZnS Quantum Dots on Blue Light-Emitting Diodes - Seo, Tae Hoon; Park, Ah Hyun; Lee, Seul Bee; Lee, Gun Hee; Kim, Myung Jong; Suh, Eun-Kyung (AMER SCIENTIFIC PUBLISHERS, 2015)
We fabricated light-emitting device by using CdSe/ZnS quantum dots (QDs) on InGaN/GaN blue light-emitting diodes (LEDs) for converting blue emission into green emission. By adding Au nanoparticles (ANPs) to generate localized surface plasmon mode, the integrated intensity of green emission of LEDs with CdSe/ZnS QDs on ANPs is enhanced by about 55%, without any drawback in electrical characteristics of LEDs. This result is attributed to an increased conversion efficiency by resonance coupling between localized surface plasmons in ANPs and excitons in CdSe/ZnS QDs.
Keywords: GENERATION; LEDS